2011
DOI: 10.1080/15567030903419430
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cadmium Selenide Thin Film for Solar Cell Application

Abstract: Thin films of cadmium selenide were prepared by thermal evaporation. The films were grown at different substrate temperatures ranging from room temperature to 300 ı C. All the films were grown under similar conditions (i.e., the chamber pressure and source current were held constant). The films were characterized optically, electrically, and structurally. The result of optical and electrical investigation shows that these films are suitable for solar cell applications. The conductivity of the film increases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The results are in agreement with earlier reported work of Velumani et al [8] and Reddy et al [26]. The texture is defined as a non-random distribution of crystal orientation [29] and texture coefficient (TC) presents the texture of a particular plane which implies the preferred growth along deviation from unity [30]. It was calculated using relation concerned and is shown in Fig.…”
Section: Structural Analysissupporting
confidence: 91%
“…The results are in agreement with earlier reported work of Velumani et al [8] and Reddy et al [26]. The texture is defined as a non-random distribution of crystal orientation [29] and texture coefficient (TC) presents the texture of a particular plane which implies the preferred growth along deviation from unity [30]. It was calculated using relation concerned and is shown in Fig.…”
Section: Structural Analysissupporting
confidence: 91%
“…It is a direct band gap semiconductor with a band gap in the visible region of the spectrum ( E g = 1.75 eV, T = 298 K). Prior work includes applications of CdSe to field-effect transistors, ,,, solar photovoltaics, photodetectors, ,, and light-emitting diodes. ,, pc -CdSe nanowires were synthesized using the lithographically patterned nanowire electrodeposition or LPNE method (Figure a,b). The process flow for the LPNE synthesis of CdSe is as follows: A nickel layer is first evaporated on a glass surface, and photoresist is deposited onto the nickel surface (Figure a,b step (i)). The nickel layer thickness will dictate the thickness of the CdSe nanowire that is electrodeposited.…”
Section: Electrodeposition Of Pc-cdse Nanowires and Nanogap Structuresmentioning
confidence: 99%
“…GIXRD data are acquired using surfaces on which linear arrays of thousands of nanowires are deposited at an interwire pitch of 5 μm (e.g., Figure 2d). An estimate of the mean grain diameter, d ave , is obtained from the GIXRD patterns using the line-width of the most intense (e.g., (111) for cubic CdSe) reflection according to the Scherrer eq: 119…”
Section: Electrodeposition Of Pc-cdse Nanowiresmentioning
confidence: 99%
“…CdSe is a direct band gap semiconductor ( E g = 1.75 eV) that has applications in electrical and photonic devices including photodetectors, ,, light-emitting diodes, ,, solar photovoltaics, and field-effect transistors. ,, Recently, we have demonstrated that field-effect transistors based upon lithographically patterned nc -CdSe nanowire arrays can be prepared, but the emission of light from polycrystalline semiconductor nanowires has not been studied at all, to our knowledge; all CdSe nanowire light-emitting devices have been prepared using single-crystalline nanowires. ,,, In this work, lithographically patterned nanowire electrodeposition (LPNE) method is used to fabricate arrays of hundreds of nanocrystalline CdSe ( nc -CdSe) nanowires with dimensions of 400–450 nm ( w ) × 60 nm ( h ) and lengths of millimeters. We compare the EL properties of nc -CdSe nanowires that were subjected to either of two post-thermal annealing processes: 300 °C × 4 h in nitrogen, and 450 °C × 1 h in nitrogen.…”
mentioning
confidence: 99%